Strengthening Institutional Model of Women-Farmers Group in Developing Household Food Diversification - Rahmadanih Rahmadanih; Sitti Bulkis; Andi Amrullah; Rusli M. Rukka; Muhammad Arsyad (Hasanuddin University, 2015)
The research objectives are (1) examining food diversification and household food security levels in the Women-Farmers Group (KWT) in rural areas and (2) analyzing the existing empowerment model of KWT and developing an alternative model of KWT based on potency. The research was conducted in Bulukumba and North Luwu Regencies, South Sulawesi, Indonesia by taking unit of analysis at household of KWT level. The findings of the research include: diversification of household food consumption in KWT in both districts is still a relatively “less diverse”; except for vegetable consumption can be said to be “quite diverse”. This is caused by the diversification program through P2KP movement and yard use activities. Generally, food diversification scores obtained KWT classified as “food insecure” (mean score = 4). The needs potential based of KWT include: an increase in group training programs; economic enterprises development and understanding on food diversification. The alternative models of KWT based on potency, needs and experiences of KWT members include (1) model of institutional support (assistance, facilities, promotion and learning process) and (2) model of human resources capacity of group members include: appropriate training and development of leadership potency to increase capability in recognizing and solving problems of food diversification and understanding on nutrition and food.